Present of occupational accidents dimensions based on risk-injury affinity groups (case study, from1384 to 1393) - Peyman Yari (Muhandisī-i bihdāsht-i ḥirfah/ī, 2017)
Background and aim: correspondence analysis method as the best method to optimize matrix functions that using the risk-injury matrix methods are analyzed. This method reduces the information contained in the risk-injury table and to determine the correlation between the variables in the matrix. The aim of this study is to present accidents and occupational hazards dimensions is dependent to risk-injury groups, using occupational accidents that can be managed.